Fluoride uptake and acid resistance of enamel irradiated with Er : YAG laser - Bevilacqua, Flavia M.; Zezell, Denise Maria; Magnani, Romeu [UNESP]; Ana, Patricia A. da; Eduardo, Carlos de Paula (Springer London Ltd, 2008)
This study evaluated the resistance to demineralization and fluoride incorporation of enamel irradiated with Er:YAG. A total of 110 bovine teeth were selected and divided into eight groups: unlased, 37% phosphoric acid, and samples irradiated with the Er:YAG laser at several fluences (31.84 J/cm(2), 25.47 J/cm(2), 19.10 J/cm(2), 2.08 J/cm(2), 1.8 J/cm(2), and 0.9 J/cm(2)). The application of acidulated phosphate fluoride was performed after treatments. All samples were immersed in 2 ml of 2.0 M acetic-acetate acid solution at pH 4.5 for 8 h, and fluoride, calcium, and phosphorus ions dissolved were analyzed by atomic absorption spectrometry and spectrophotometry. The phosphoric acid and 31.84 J/cm(2) groups presented the lowest dissolution of calcium and phosphorus ions. Higher fluoride incorporation was observed on 1.8 J/cm(2) and 0.9 J/cm(2) groups. Based on these results, Er:YAG laser was able to decrease acid dissolution and increase fluoride uptake and can be a promissory alternative for preventive dentistry.
Keywords: laser; enamel; demineralization; fluoride